Factors influencing image quality in Tibetan children by optical coherence tomography - Yao Yao; Jiawen Liu; Lei Li; Weiwei Chen; Zhaojun Meng; Jing Fu (Frontiers in Medicine)
PurposeThis study aim to investigate the clinical findings of subjects characteristics and image quality related factors in Tibetan children by optical coherence tomography (OCT) in epidemiological cohort study.MethodsParticipants were 1,856 first-grade students (mean age = 6.82 ± 0.46 years) from seven selected elementary schools in Lhasa. Following comprehensive systemic and ophthalmic examinations, OCT scans were assessed by specialists with manual segmentation as needed.ResultsA total of 1,698 students completed the examination protocol in this study (91.5%). After manual screening, 1,447 (78%) and 1,289 (70%) images could be analyzed in the macular and optic disc regions, respectively. Common image flaws were blinking or fixation error (70%+), poor focusing, and positioning errors. Among students who have completed OCT, a higher percentage of boys (X2 = 8.48, P = 0.004) and suburban students (X2 = 34.97, P < 0.001) with younger age (t = -2.20, P = 0.03), worse near vision (t = -3.95, P < 0.001), higher IOP (t = 2.38, P = 0.017) and higher heart rate (t = 3.15, P = 0.002) have unsatisfactory image quality in the macular region, almost same as the optic disc region. Students in suburban schools (OR = 1.74, P < 0.001) with lower near VA (OR = 6.64, P < 0.001) or boys (OR = 0.78, P = 0.03) were more likely to have worse image quality on OCT scans when corrected for ethnicity. Manual segmentation was more prevalent in the optic disc region, resulting in increased retinal thickness across most subregions.ConclusionThis study underscores the imperative for stringent image quality control in pediatric OCT assessments to ensure precise clinical outcomes.